Competency Strategy for SMA and SMK Teachers (Education Office of West Java Province) - Karna Husni; Imas Herlina; Nu'man Sidik; Dedi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This study aims to find out how to improve the quality of teachers at the SMA and SMK education levels in West Java. This study uses a literature review approach by taking data from the results of the Study on Increasing Teacher Professionalism in Facing Learning in the Industrial Revolution 4.0 Era Regional Research and Development Agency for West Java Province in 2022, Profile Book of the West Java Education Office in 2021 and relevant journals. Based on the results of research that has been done, the fact is obtained that 46% of high school, vocational and special school teachers in West Java Province have professionalism at the Cakap Level. In fact, there are 36% of teachers who are already at the Advanced Level. Even so, there are still 19% of teachers in West Java Province who have not met the standard of teacher professionalism. In order to realize Champion Teachers in West Java, the West Java Provincial Education Office strives for Professional Teachers who can develop the potential of students to become human beings with character and competence in realizing happy, prosperous students by implementing 4 Strategies, namely: 1. 1). Fulfillment of Teacher Competency and Career, 2). Equal distribution of teacher and student ratios, through the development of the Teacher and Education Personnel Data Information System Application, 3). GTK Award and Protection; and 4). Fulfillment of Teacher Allowances